The effects of a South African Black youth jive on selected biophysical physiological and psycho-social parameters - Masipa, Mochaki Deborah (Rhodes University, Faculty of Science, Department of Human Movement Studies, 1989)
This study investigated the effects of a South African Black youth jive on selected Biophysical, Physiological and Psycho-social parameters, using 31 Black youths, males and females (mean age 19.29 yrs) as subjects. All subjects participated in the pre- and post-programme testing protocols (acting as their own control) and in a 7-week jive programme. While the female subjects were significantly (p<0.05) heavier with a greater percentage body fat than their male counterparts, a two factor analysis of variance revealed no significant changes in body composition (p<0.05) of either sex group. However, significant improvements did occur in the cardio-respiratory . parameters of working and recovery heart rates, predicted V0â‚‚ max, and the anaerobic capacity. Here, the males exhibited superior cardio-respiratory qualities and performed better in all motor fitness parameters except flexibility, where no significant sex difference occurred. Also, there were significant improvements in all motor fitness tests with the exception of power (as tested in the 18-Item Illinois test). No significant differences occurred between male and female psycho-social responses with no changes occurring after the 7- week programme. It can be concluded that involvement in the 7-week jive programme improved physiological parameters but failed to bring about alterations in the biophysical and psycho-social domains..
Keywords: Movement, Psychology of; Dance, Black -- Physiological aspects; Dance -- Physiological aspects